Respuestas

2013-06-08T00:59:48+02:00
A‐2B 
A
= – [2‐ (‐12) + (3‐2) ‐ 5(4‐3)]
A= 
 – [2 + 12 + 1 - 5(1)]
A=  – [10]
A= – 10
B= 5 – {2 ‐(15:(5 ‐ 2)) * (‐5)} + {2 ‐ 3 (10  ‐2)} ‐ {5 ‐ 3 + 2 ‐ 1}
B= 5 – {2 ‐(5) * -5} + {2 - 3(8)} ‐ {3}
B= 5 – { - 3 * - 5 } + {2 - 24 } ‐ 3
B=5 – { 15 } + { - 22 } ‐ 3
B= 5 - 15 - 22 - 3
B= 35

A‐2B
-10 - 2(35)
-10 -70
-80
2013-06-08T01:02:54+02:00
A= – [2‐ (‐12) + (3‐2) ‐ 5(4‐3)],B= 5 – {2 ‐(15:(5 ‐ 2) * (‐5)} + {2 ‐ 3 (10  ‐2)} ‐ {5 ‐ 3 + 2 ‐ 1}
A= – [2‐ (‐12) + (3‐2) ‐ 5(1)],B= 5 – {2 ‐(15:(5 ‐ 2) * (‐5)} + {2 ‐ 3 (10  ‐2)} ‐ 3
A= – [2‐ (‐12) + (3‐2) ‐ 5)],B= 5 – {2 ‐(15:(5 ‐ 2) * (‐5)} + -8 -3
A= – [2‐ (‐12) + (1) ‐5 ],B= 5 – {2 ‐(15:( 3 ) *-5} + -8 -3
A= – [2‐ (‐12)  ‐5 ],B= 5 – {2 ‐(-15)} + -11
A= – [2 + 60],B= 5 – 17 -11
A= -62
B= -22
A - 2B = -62 - 2(-22) = -62 + 64 = 2